2022
DOI: 10.3390/polym14122330
|View full text |Cite
|
Sign up to set email alerts
|

Flow Behaviors of Polymer Solution in a Lid-Driven Cavity

Abstract: In this work, a numerical study of polymer flow behaviors in a lid-driven cavity, which is inspired by the coating process, at a broad range of Oldroyd numbers (0≤Od≤50), is carried out. The Reynolds number is height-based and kept at Re=0.001. The fluid investigated is of Carbopol gel possessing yield stress and shear-thinning properties. To express rheological characteristics, the Herschel–Bulkley model cooperated with Papanastasiou’s regularization scheme is utilized. Results show that the polymer flow char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Most open-cavity-flow studies have carried out flow and pressure data collection by visualization facilities [5]. Corresponding results have shown that a feedback mechanism of the shear layer-cavity corner having obvious impacts on the unsteady turbulent flow in the cavity is the intrinsic characteristic over a considerable quantity of Reynolds (Re) and Mach numbers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most open-cavity-flow studies have carried out flow and pressure data collection by visualization facilities [5]. Corresponding results have shown that a feedback mechanism of the shear layer-cavity corner having obvious impacts on the unsteady turbulent flow in the cavity is the intrinsic characteristic over a considerable quantity of Reynolds (Re) and Mach numbers [6].…”
Section: Introductionmentioning
confidence: 99%